2017 32nd IEEE/ACM International Conference on Automated Software Engineering (ASE) 2017
DOI: 10.1109/ase.2017.8115695
|View full text |Cite
|
Sign up to set email alerts
|

Test suite parallelization in open-source projects: A study on its usage and impact

Abstract: I would not make this far without the help and support from some people that have followed me in this journey. I am a very fortunate person for having such wonderful parents. They have always trusted me and gave me the necessary support and freedom to chase my dreams. I dedicate this work to my family for being always present in my file, in the bad and good moments, and always will be my reference. Everything that I've accomplished so far would not be possible without their unconditional support, and I will ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Moreover, we present the percentage of open source projects whose internationalization effort are high/low across various programming languages, which is illustrated in Fig. 6 . Note that programming languages that are only used by one or two projects are omitted in the figures.…”
Section: Rq3: What Factors Influence the Internationalization Effort Of Projects Open Sourced By Bat?mentioning
confidence: 99%
“…Moreover, we present the percentage of open source projects whose internationalization effort are high/low across various programming languages, which is illustrated in Fig. 6 . Note that programming languages that are only used by one or two projects are omitted in the figures.…”
Section: Rq3: What Factors Influence the Internationalization Effort Of Projects Open Sourced By Bat?mentioning
confidence: 99%
“…Candido et al [3] investigate how common concurrent test executions are in open source projects. Their results show that only 13 out of 110 investigated Java projects execute tests concurrently.…”
Section: Related Workmentioning
confidence: 99%
“…In order to solve this issue, test parallelization has been proposed as a solution. Recently, Candido et al [11] conducted an empirical survey on the impact of test suite parallelization in open source projects. The authors reported that only 19.1% of the projects analyzed use parallelization, being the major deterrent to its adoption the resistance concerning concurrency issues.…”
Section: B Test Parallelizationmentioning
confidence: 99%
“…ElasTest follows a microservices approach, and the component which is responsible for discovering and operating the different services that ElasTest make available to tests is called ElasTest Service Manager (ESM). This component is based on the Open Service Broker API (OSBA) 11 for discovering, registering and unregistering services within the platform. RabbitMQ 12 is used as messaging queue for the events communication among the different services.…”
Section: A Elastest In a Nutshellmentioning
confidence: 99%